Results of motor abilities and anthropometric and functional characteristics of physical preparedness of students-powerlifters with musculoskeletal diseases with different experience of taking exercises - Лобко Віталій Станіславович, (Vitaly Lobko) (Slobozhanskyi Herald of Science and Sport, 2015)
Our investigation dedicates to the problem of improving students’ health. Particularly, it refers to find out the ways of increasing students-powerlifters’ health with musculoskeletal diseases based on powerlifting. Purpose: to study the influence of long – term powerlifting exercises on anthropometric and functional characteristics and motor abilities of students- powerlifters with musculoskeletal diseases. Material and Methods: methods of investigation: theory analysis, synthesis and generalization, testing and math’s statistics and pedagogical experiment. There are 73 students with musculoskeletal diseases with different experience of taking exercises, 21 – had 1 year experience, 18 – 2 years, 12 – 3 years, 11 – 4 years and 11 – 5 years. Results: there are the differences of anthropometric and functional characteristics and the results of developing students’ motor abilities with different experience of taking exercises. Conclusion: the investigation revealed that increasing of the students’ sportsmanship shows the great growth almost all the investigated results.